Willingness to pay for air quality improvements in Klang Valley Malaysia - Afroz, Rafia; Hassan, Mohd Nasir; Awang, Muhamad; Ibrahim, Noor Akma (Science Publications, 2005)
This research employed contingent valuation method (CVM) to estimate the willingness to pay (WTP) of the respondents to improve the air quality in Klang Valley. The samples were divided according to different question formats i.e. open ended(OE), dichotomous choice(DC) and payment card(PC). The objective of this study is to investigate the convergent validity of contingent valuation estimates by comparing the WTP values of different question formats. The comparison of responses to different question formats in terms of positive response rate, valid zero, rejection of contingent market was carried out using the z-tests. Paired t-tests of equivalent means were also conducted to test the equality of the mean value of the WTP of the respondents for different question formats. The results of the study suggested that the WTP values of the respondents do not differ significantly across different question formats and the WTP values of the respondents using the DC format were the highest. However due to the nature of the question format, the mean WTP values using the DC method would normally be higher than those of OE and PC. The aggregate WTP value of the respondents was RM0.91 billion for air quality improvement in Klang Valley.